(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study investigated the impact of post-harvest storage methods (moist sawdust and trench storage) on the functional properties of starch extracted from bitter (TMS 30572) and sweet (TMS 4(2)1425) cassava varieties over a six-week period. Key functional properties analyzed included water absorption capacity, bulk density, swelling index, least gelation concentration (LGC), and pasting behavior using Rapid Visco Analyzer (RVA). Starch from both varieties showed no initial swelling potential (0 weeks) but exhibited gradual increases in swelling index during storage, influenced by starch-water hydrogen bonding and structural differences. Bulk density increased progressively across all samples, correlating with improved wettability and sink ability for industrial applications. Water absorption capacity remained lowest in starch products, attributed to variations in amylose/amylopectin ratios and granule size. LGC trends revealed divergent behavior: starch from sweet cassava stored in moist sawdust (SDSCS) showed consistent gelation improvement, while other samples fluctuated, reflecting interactions between starch constituents and storage-induced biochemical changes. Pasting properties demonstrated dynamic changes, with peak viscosity decreasing initially (0–2 weeks) due to microbial alteration of starch structure, followed by recovery (4–6 weeks). Moist sawdust storage better preserved functional integrity, particularly for sweet cassava, which displayed higher peak viscosity stability. Trench-stored samples exhibited greater variability, likely due to environmental exposure. The study concluded that moist sawdust storage optimizes functional properties for industrial use, mitigating post-harvest deterioration while enhancing starch quality. These findings provide actionable insights for small-scale farmers and cassava processors to reduce losses, improve food safety, and increase market value through tailored storage practices.